2013
DOI: 10.3892/or.2013.2915
|View full text |Cite
|
Sign up to set email alerts
|

Allograft inflammatory factor-1 is an independent prognostic indicator that regulates β-catenin in gastric cancer

Abstract: Previous studies have revealed that expression of allograft inflammatory factor-1 (AIF-1) protein appears to be increased in malignancies and is correlated with a poorer prognosis in cervical cancer, while its role in gastric cancer has not been reported. We analyzed the expression of AIF-1 in 78 cancer lesions and the corresponding non-cancerous tissues by immunohistochemistry. In contrast with other cancers, we found that AIF-1 protein levels were significantly decreased in 53 of the 78 (67.9%) gastric cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…These previous studies support the possibility that AIF-1 acts as an oncogene. However, in contrast to our findings, Ye et al showed significantly lower AIF-1 protein levels in gastric cancer tissues than in matched adjacent non-cancerous tissues and provided novel evidence of a negative correlation between AIF-1 expression and clinical and histopathological parameters [ 32 ]. These data suggest that the mechanisms by which AIF-1 is involved in cancer progression remain unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…These previous studies support the possibility that AIF-1 acts as an oncogene. However, in contrast to our findings, Ye et al showed significantly lower AIF-1 protein levels in gastric cancer tissues than in matched adjacent non-cancerous tissues and provided novel evidence of a negative correlation between AIF-1 expression and clinical and histopathological parameters [ 32 ]. These data suggest that the mechanisms by which AIF-1 is involved in cancer progression remain unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…Only very recently, it was shown that AIF1L is highly expressed in conditions of breast cancer and correlates with proliferation behavior via modulation of cyclin-D1 levels [ 16 ]. These findings are in accordance with previous reports about the role of AIF1 in cancer and breast cancer in particular [ 41 , 44 , 45 ]. In the context of podocytes, a recent study identified Aif1l with several other genes highly enriched in murine podocytes using single cell RNA-Seq approaches [ 14 ].…”
Section: Discussionsupporting
confidence: 94%
“…EF-hand (EFh) domain-containing proteins are associated with numerous disease states, including chronic inflammation and tumor progression [12]. The AIF1L protein structure encompasses two central EFh motifs that lack bound Ca 2+ [18]. AIF1L is expressed at high levels in kidney tissues.…”
Section: Discussionmentioning
confidence: 99%
“…EF-hand (EFh) domain-containing proteins have been implicated in malignant progression [12]. Allograft inflammatory factor 1 (AIF1, also referred to as IBA1) contains Efh and plays a critical role in the initiation and progression of cancers [13][14][15][16][17][18]. AIF1L (allograft inflammatory factor 1like, also referred to as IBA2) is a homolog of AIF1 [19,20] and has a similar overall structure and molecular function [20].…”
Section: Introductionmentioning
confidence: 99%